THE URGENCY OF UNDERSTANDING SHARI'A IN THE GENERAL Z ERA - Nasiri (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2023)
This research is a library research with a qualitative approach. The data collection technique in this study uses documentary techniques, while the methods used are content analysis and interpretation. This study aims to determine the urgency of Islamic religious education in the era of globalization. The results of this research are: The urgency of Islamic religious education in the era of globalization is as a foundation for minimizing moral degradation and creating human resources with noble character. Islamic religious education is a solution to moral degradation because Islamic religious education aims to shape people with morals and prepare competent individuals by mastering religious knowledge and science.